2019
DOI: 10.1038/s41396-019-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Marked changes in diversity and relative activity of picoeukaryotes with depth in the world ocean

Abstract: Microbial eukaryotes are key components of the ocean plankton. Yet, our understanding of their community composition and activity in different water layers of the ocean is limited, particularly for picoeukaryotes (0.2-3 µm cell size). Here, we examined the picoeukaryotic communities inhabiting different vertical zones of the tropical and subtropical global ocean: surface, deep chlorophyll maximum, mesopelagic (including the deep scattering layer and oxygen minimum zones), and bathypelagic. Communities were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
116
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 57 publications
(94 reference statements)
13
116
1
Order By: Relevance
“…The image retrieved in our study on the picosized fraction was broadly similar to that reported in Giner et al (2020) using V4 rDNA amplicons, with MALV groups dominating the photic zone along with Dinoflagellata, Pelagophyceae and Prymnesiophyceae, although this last group was only detected by metagenomics and represented a critical difference. In the aphotic layer, both approaches revealed a dominance of MALV, Polycystinea, Acantharia, and RAD‐B, together with Diplonemea only detected by metagenomics.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The image retrieved in our study on the picosized fraction was broadly similar to that reported in Giner et al (2020) using V4 rDNA amplicons, with MALV groups dominating the photic zone along with Dinoflagellata, Pelagophyceae and Prymnesiophyceae, although this last group was only detected by metagenomics and represented a critical difference. In the aphotic layer, both approaches revealed a dominance of MALV, Polycystinea, Acantharia, and RAD‐B, together with Diplonemea only detected by metagenomics.…”
Section: Discussionsupporting
confidence: 88%
“…V4 amplicon sequences. Deposited at European Nucleotide Archive, accession number PRJEB23771, from a previous study (Giner et al, 2020). V9 amplicon sequences.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The hadal zone (exclusively comprised of trenches) constitutes the deepest 45% of the vertical depth of the global ocean ( Jamieson et al, 2010 ; Jamieson, 2015 ) and was known to host active and diverse biological communities ( Jamieson et al, 2010 ; Nunoura et al, 2015 ; Xu et al, 2018 ; Liu et al, 2019b ), indicating the hadal ecosystem is crucial to ocean food web. Previous surveys on the distribution of microbial eukaryotes along the water column on a global scale ( Giner et al, 2020 ) and in specific oceanic regions ( Countway et al, 2007 ; Not et al, 2007 ; Brown et al, 2009 ; Hu et al, 2016 ; Xu et al, 2017 ) have revealed unexpected high phylogenetic diversity of microbial eukaryotes in deep seas and a clear differentiation between surface photic and deep aphotic ocean communities. However, the maximum depth of these studies was limited to the bathypelagic zone.…”
Section: Introductionmentioning
confidence: 99%
“…While the "paradox of the plankton" and its resolution based on the theory of chaos support the co-occurrence of functionally similar plankton (Huisman & Weissing, 1999;Hutchinson, 1961), here we show that indeed phylogenetic related plankton co-occur but could simultaneously co-exclude themselves more than expected by chance at the marine surface. Other large-scale processes affect the assembly patterns of marine sunlight exposure and currents responsible of the depth stratification in the water column (Giner et al, 2020;Ibarbalz et al, 2019). However, geographical structures, natural fluctuations and absence of equilibrium state in marine plankton communities are not enough to avoid exclusion among related organisms, as observed here, and would refute the existence of any plankton paradox under phylogenetic niche conservatism.…”
Section: Discussionmentioning
confidence: 70%